2021
DOI: 10.1163/2165025x-bja10017
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Presidential Satisfaction: Preliminary Insights from Survey Data on the Bottom Poor in Metro Manila

Abstract: Measures of presidential satisfaction have long been in the public’s attention, but the factors that drive them have brought about much discussion. As a contribution to the literature, this study empirically examines presidential approval data in the Philippines using a unique survey of 1200 low-income voting age residents of Metro Manila. Using individual-level data, this study unpacks the possible factors underpinning survey results on citizens’ satisfaction with leadership in the Philippines. While accounti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our hypothesis concerning social conformity pressure resembles what Canare et al (2021) labeled “herd behavior.” Economists and sociologists use this term to refer to the phenomenon of people following a crowd. Canare et al's (2021) survey research, conducted among Metro Manila residents, found that respondents who believed the president was popular among people they knew were more likely to support him than those who did not.…”
Section: The Puzzle Of Popular Backsliding Incumbentssupporting
confidence: 72%
See 2 more Smart Citations
“…Our hypothesis concerning social conformity pressure resembles what Canare et al (2021) labeled “herd behavior.” Economists and sociologists use this term to refer to the phenomenon of people following a crowd. Canare et al's (2021) survey research, conducted among Metro Manila residents, found that respondents who believed the president was popular among people they knew were more likely to support him than those who did not.…”
Section: The Puzzle Of Popular Backsliding Incumbentssupporting
confidence: 72%
“…Our hypothesis concerning social conformity pressure resembles what Canare et al (2021) labeled "herd behavior." Economists and sociologists use this term to refer to the phenomenon of people following a crowd.…”
Section: H2mentioning
confidence: 57%
See 1 more Smart Citation
“…Moreover, receiving support from host countries can potentially free them from dependence on the Philippine government for benefits and repatriation. Findings from the study of Canare et al (2021) indicated that access to alternative sources of credit from sources aside from the government can decrease clientelistic ties from incumbent politicians among Filipinos and encourage critical presidential evaluations. When OFWs receive aid from host countries, they may be more likely to evaluate the Philippine government more objectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, aid from the host country may make OFWs less dependent on the Philippine government. It has been shown that having an alternative source of emergency funds that does not belong to the government is linked with more candid evaluations of the president in the Philippines (Canare et al, 2021). With assistance from the host country potentially lessening the legitimacy-building effect of ayuda from the Philippines, we hypothesize that:…”
Section: Review Of Relevant Literaturementioning
confidence: 99%